(untitled) ("Journal "U". Economy. Management. Finance.", 2022)
This article analyzes the import of cars from the UAE to Russia. A scheme for the purchase and delivery of cars to Russia is presented, a comparative table of the cost of models is given, and the positive and negative aspects of this import operation are analyzed. A conclusion is given on the expediency of this import for the consumer and for business. The results obtained can be used for further research in the field of consumer goods imports, as well as for developing recommendations for commercial organizations.